PENGARUH UKURAN PERUSAHAAN, UKURAN DEWAN KOMISARIS, LEVERAGE DAN KINERJA LINGKUNGAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) (Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di BEI 2014-2016) - Fischa Permata Dwiyandra; Alfiati Silfi; Lila Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to examine the effect of firm size, board size, leverage and environmental performance on Corporate Social Responsibility Disclosure on mining companies listed on Indonesia Stock Exchange 2014-2016. This research is conducted on companies that are included in mining companies with observation period during 2014 - 2016. Analysis technique is done by multiple linear regression analysis technique. Sample selection in this study using purposive sampling method where the company to be studied must meet certain criteria. The number of companies used as research samples based on predetermined criteria are 16 companies. And hypothesis testing using t test to test the coefficient partially with significant level 5%. In addition, the data normality test, classical assumption test which includes normality test, autocorrelation test, multicolinearity test, and heterokedastisity test. The results of this study show that the size of the board of commissioners, leverage and environmental performance affect the disclosure of Corporate Social Responsibility. While the size of the company does not affect the Corporate Social Responsibility Disclosure.Keywords : firm size, Board size, Leverage, environmental performance and Corporate Social Responsibility Disclosure